Studi Literatur: Pengaruh Ragam Model Pembelajaran terhadap Kemampuan Berpikir Kritis Peserta Didik SMA : Literature Study: The Influence of Various Learning Models on High School Students' Critical Thinking Skills - Sisri Wiguna; Ganda Hijrah Selaras (Al-Alam: Islamic Science Education Journal, 2025)
Critical thinking skills are very important in the Biology learning process because they enable students to understand concepts in depth, analyze natural phenomena, and solve problems logically. This study aims to determine the effect of various learning models on students' critical thinking skills in Biology. The method used in this study was a literature review by collecting and analyzing 10 articles published between 2017 and 2024. The results of the study indicate that critical thinking skills in Biology learning can be influenced by various learning models that can improve students' critical thinking skills. Learning models such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), and Discovery Learning have been proven effective in improving critical thinking skills.